Knowledge of Physical Activity Guidelines and Its Association with Physical Activity and Physical Function in Older Adults. Issue 2 (2nd April 2020) - Cheung, C.; Talley, K. M; McMahon, S.; Schorr, E.; Wyman, J. F.
ABSTRACT: Older Minnesota State Fair attendees age ≥55 years were recruited to determine if physical activity (PA) guideline knowledge was associated with self-reported PA behavior and physical function. Survey data and repeated chair stands scores were collected and analyzed using logistic regression models. Participants (n = 434) were college educated (75%), women (58%) with a mean age of 65 ± 7 years. Knowledge of PA guidelines was not related to higher PA levels or better physical function. Having adequate self-reported aerobic activity levels was associated with physical function ( p = .02). Better physical function ( p = .01), lower body mass index ( p = .03) and good general health ( p < .0001) were associated with meeting PA guidelines. Health promotion efforts should focus on providing opportunities and resources for older adults to actually engage in PA.